Analysis of tactics and offensive play systems at the European elite teams in order to optimize the attack of the Romanian top teams - men`s handball - Prisacaru, R. (EHF Scientific Conference 18.-19.11.2011, Wien, Österreich, 2011)
The research falls into the process of performance capacity optimization through the technical and tactical component seen by the application of offensive play systems against different collective defense structures and approach of attack against defenses under retreat and reorganization. We focussed on the team actions from a tactical point of view, in other words, how they are developed between the beginning and the end of a game phase, considering the ratio of opposition between many teams.